Ultrafast Dynamics of a Nucleobase Analogue Illuminated by a Short Intense X-ray Free Electron Laser Pulse - K. Nagaya; K. Motomura; E. Kukk; H. Fukuzawa; S. Wada; T. Tachibana; Y. Ito; S. Mondal; T. Sakai; K. Matsunami; R. Koga; S. Ohmura; et al. (AMER PHYSICAL SOC, 2022)
Understanding x-ray radiation damage is a crucial issue for both medical applications of x rays and x-ray free-electron-laser (XFEL) science aimed at molecular imaging. Decrypting the charge and fragmentation dynamics of nucleobases, the smallest units of a macro-biomolecule, contributes to a bottom-up understanding of the damage via cascades of phenomena following x-ray exposure. We investigate experimentally and by numerical simulations the ultrafast radiation damage induced on a nucleobase analogue (5-iodouracil) by an ultrashort (10 fs) high-intensity radiation pulse generated by XFEL at SPring-8 Angstrom Compact free electron Laser (SACLA). The present study elucidates a plausible underlying radiosensitizing mechanism of 5-iodouracil. This mechanism is independent of the exact composition of 5-iodouracil and thus relevant to other such radiosensitizers. Furthermore, we found that despite a rapid increase of the net molecular charge in the presence of iodine, and of the ultrafast release of hydrogen, the other atoms are almost frozen within the 10-fs duration of the exposure. This validates single-shot molecular imaging as a consistent approach, provided the radiation pulse used is brief enough.